An investigation on different factors influencing perceived organizational change - Abbas Saleh Ardestani; Kaveh Teymournezhad; Sajad Ahmadvand (Management Science Letters)
This paper studies the impacts of different factors influencing on perceived organization change in municipality organization in city of Tehran, Iran. The proposed study uses two questionnaires, one for measuring the effects of five factors including partnership, communication, training, believe in change and organization commitment and the other for organizational change in Likert scale. The study has been implemented among 147 regular employees of municipality organization in city of Tehran, Iran. Using simple regression analysis, the study has detected that all mentioned factors influence organizational change, positively. In addition, Freedman test indicates that partnership maintains the highest impact followed by believe in change, communication, organizational commitment and training.